How do parents influence their adolescents' use of over‐the‐counter analgesics: A review of the current literature. Issue 9 (13th February 2019) - Skarstein, Siv; Lagerløv, Per; Helseth, Sølvi; Leegaard, Marit
Abstract: Aim and objectives: Continuous use of over‐the‐counter analgesics (OTCAs) may prevent adolescents from learning healthier options and might lead to lifelong use of such medicines. It is possible that parents' own use of OTCAs might influence adolescents, but little is known about this issue. Our research questions were; "What are the main factors leading to a high use of OTCAs among adolescents and how can health professionals support these adolescents in their pain management?" Background: Frequent consumption of OTCAs may cause health problems such as drug‐induced headache and liver failure. Some adolescents frequently use non‐prescribed pain medication and their attitudes towards the use of OTCAs vary from responsible to careless. Design: A "systematic search and review" was conducted between March 2017 and May 2018. Quantitative and qualitative studies were included. Methods: We used the PRISMA Statement checklist, the PRISMA flow diagram and The Critical Appraisal Skills Programme for quality appraisal. Our search identified 3, 386 possible sources, 2, 043 articles were selected for title examination, and 70 articles underwent abstract review. Fourteen articles were reviewed entirety. Ten articles were of acceptable quality. Results: The importance of parental influence on adolescent use of OTCAs is significant. These findings seem to be independent of country and culture. Conclusion: Parents are the most important source of information regarding the use of OTCAs; further, they are the main supplier of the medicine. A broad understanding of human development, health, pain and use of pain medication is needed to develop targeted information and support adolescents with high consumption of non‐prescription pain medication. Relevance to clinical practice: I nformation from professionals such as school nurses is important. Professionals must consider the physical, social and psychological aspects influencing the use of OTCAs. Information should be made available to adolescents, parents and society in general.